Vitamin D and Traumatic Brain Injury: A Systematic Review of Preclinical Evidence - Jaslindo, Lieka Nugrahi; Sari, Widia; Dhuha, Alief; Handayani, Kurnia Maidarmi; Khudri, Ghaniyyatul Nugrahi; Maribeth, Annisa Lidra (Health and Medical Journal, 2026)
Traumativ Brain Injury (TBI) triggers multiple secondary injury processes, such as inflammation, oxidative stress, apoptosis, BBB disruption, and impaired autophagy. These mechanisms contribute to progressive neuronal damage and functional decline. Vitamin D has emerged as a potential multi-target neuroprotective agent due to its regulatory roles in immune signaling, oxidative balance, neuronal survival, and autophagy pathways. This systematic review synthesized preclinical evidence evaluating the effects of Vitamin D supplementation in animal models of TBI. A comprehensive search of PubMed, OVID, and ProQuest identified six eligible studies. Across diverse dosing regimens and formulations, Vitamin D consistently improved key TBI outcomes. Reported benefits included reduced apoptosis, decreased neuroinflammation, attenuation of oxidative stress, preservation of BBB integrity, restoration of autophagy flux, and enhanced cognitive performance. Mechanistically, Vitamin D influenced several pathways, including Nrf2 activation, TLR4/MyD88/NF-κB suppression, mTOR and TRPM2 normalization, and improved microglial polarization. Although methodological quality varied, most studies demonstrated moderate rigor and supported the neuroprotective actions of Vitamin D. Heterogeneity in injury models, dosing strategies, and outcome measures limits direct comparison and highlights the need for standardized experimental approaches. Overall, current preclinical evidence indicates that Vitamin D confers robust neuroprotection following TBI. Further studies examining its mechanistic pathways, optimal therapeutic windows, and translational potential are warranted to inform future clinical applications.